2019
DOI: 10.1002/bit.27081
|View full text |Cite
|
Sign up to set email alerts
|

Control of antibody high and low molecular weight species by depth filtration‐based cell culture harvesting

Abstract: Depth filtration-based harvesting is widely used in mAb manufacturing to remove cell and process-related impurities. However, it has not been studied on control of product-related impurities, which are very critical for product quality. In this article, we studied the interactions of depth filter with high and low molecular weight species (HMWs and LMWs) for their direct removal from cell culture. The process parameters (filter, loading, temperature, and flux) were evaluated for adsorption of HMWs and LMWs by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“… 18 However, when compared to the group previous work, 19 they conclude that different depth filter media has different capacities for model protein solutions and some filters may be used to remove specific sub‐classes of HCP. A direct comparison of X0HC and X0SP 20 showed that X0SP had a 50% higher binding capacity when model protein solutions were used, crediting the improved charge functionality on the X0SP. An increased hydrophobic score was also linked to the reduction of high and low molecular weight mAb species, 21 though the filter media and filter loading were the biggest factors for this.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“… 18 However, when compared to the group previous work, 19 they conclude that different depth filter media has different capacities for model protein solutions and some filters may be used to remove specific sub‐classes of HCP. A direct comparison of X0HC and X0SP 20 showed that X0SP had a 50% higher binding capacity when model protein solutions were used, crediting the improved charge functionality on the X0SP. An increased hydrophobic score was also linked to the reduction of high and low molecular weight mAb species, 21 though the filter media and filter loading were the biggest factors for this.…”
Section: Resultsmentioning
confidence: 91%
“…A direct comparison of X0HC and X0SP 20 showed that X0SP had a 50% higher binding capacity when model protein solutions were used, crediting the improved charge functionality on the X0SP. An increased hydrophobic score was also linked to the reduction of high and low molecular weight mAb species, 21 though the filter media and filter loading were the biggest factors for this.…”
Section: Flux and Impurity Breakthroughmentioning
confidence: 91%
“…Centrifugation, depth filtration, and tangential flow microfiltration (TFF-MF) are the most commonly used techniques for cell harvesting and cell separation (Besnard et al, 2016;Voulgaris et al, 2016;Richardson and Walker, 2018;Carvalho et al, 2019b;Yu et al, 2019). The various clarification technologies used for the downstream processing of antibodies have been described elsewhere (Singh et al, 2016;Singh and Chollangi, 2017).…”
Section: Downstream Process Developmentmentioning
confidence: 99%
“…For example, researchers have used reduced and non‐reduced SDS‐CGE for analyzing fractionated mAb acidic variants to identify their fragment composition [93]. Non‐reduced SDS‐CGE was also reported to quantitate low molecular weight species in mAb producing cell harvest samples [94]. Microfluidic SDS‐CGE was used as an orthogonal method to high‐performance size exclusion chromatography (HP‐SEC) for mAb fragmentation analysis and revealed more accurate molecular weight estimation than HP‐SEC [89].…”
Section: Ce‐based Characterization Of Critical Quality Attributes (Cq...mentioning
confidence: 99%